2020
DOI: 10.1186/s12935-020-01519-x
|View full text |Cite
|
Sign up to set email alerts
|

circRAE1 promotes colorectal cancer cell migration and invasion by modulating miR-338-3p/TYRO3 axis

Abstract: Background: Growing evidence has revealed the involvement of circular RNAs (circRNAs) in numerous carcinogenesis. However, the role of circRNAs in the cancer biology of colorectal cancer (CRC) remains vague. Methods: Quantitative RT-PCR was used to detect the expression level of circRAE1 in CRC tissues and CRC cell lines. Cell proliferation, migration, and invasion were detected using CCK8 assay, Colony formation assay, wound-healing and Transwell assays. The interaction between circRAE1 and miR-338-3p and TRY… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The cell migration was detected as set forth [ 13 ]. Transwell chamber (Corning, U.S.) was applied in this assay.…”
Section: Methodsmentioning
confidence: 99%
“…The cell migration was detected as set forth [ 13 ]. Transwell chamber (Corning, U.S.) was applied in this assay.…”
Section: Methodsmentioning
confidence: 99%
“…There was an increased level of cir-cRAE1 in CRC tissues that was correlated with advanced TNM stage, tumor size, and lymph node involvement. It also promoted colorectal tumor cell migration by miR-388-3p sponging to upregulate TYRO3 [32]. RAB14 is an oncogenic GTPase involved in cell proliferation and invasion through regulation of the AKT pathway [33,34].…”
Section: Circular Rnasmentioning
confidence: 99%
“…Due to the unique circular closed structure, high stability, and special expression patterns, it is believed that circRNAs can become potential biomarkers (25). In fact, circRNAs are dysregulated in various cancers, including LUACs (26)(27)(28). Several studies have suggested that dysregulated circRNAs in tissues or plasma could be used as novel biomarkers for cancer (29,30).…”
Section: Discussionmentioning
confidence: 99%